Imatinib melylate as second‐line treatment of bronchiolitis obliterans after allogenic hematopoietic stem cell transplantation in children. Issue 3 (17th January 2020) - Faraci, Maura; Ricci, Erica; Bagnasco, Francesca; Pierri, Filomena; Giardino, Stefano; Girosi, Donata; Olcese, Roberta; Castagnola, Elio; Michele Magnano, Gian; Lanino, Edoardo
Abstract: Background: The onset of bronchiolitis obliterans (BO) as a pulmonary manifestation of chronic graft vs host disease dramatically changes the prognosis of children undergoing allogeneic hematopoietic stem cell transplantation (allo‐HSCT). This study aimed to evaluate the overall survival (OS) of children with BO treated with imatinib mesylate (IM). Methods: This study included children who underwent allo‐HSCTs between January 2000 and December 2016. Results: Among 345 patients who underwent HSCTs, 293 were evaluable for BO and 26 (8.9%) developed BO. The cumulative incidence of BO was 4.8% (95% confidence interval [CI], 2.8‐7.5) at 1 year and 7.7% (95% CI, 5.1‐11.1) at 3 years after transplantation. In the group of HSCTs (n = 67) complicated by chronic GvHD (c‐GVHD), the incidence rate of BO was 38.8%. In total, 96.1% of patients with BO had c‐GvHD worse than moderate grade, which was present in 70.7% of patients without BO ( P  = .011). The mortality rates were 46.1% in the BO group and 27.4% in the group without BO. Half of the patients with BO (n = 13) received IM, and the overall response rate was 76.9%. Four years after HSCT, OS was 42.6% (95% CI, 18.2‐65.3) in the group without IM and 83.3% (95% CI, 27.3‐97.5) in the group with IM. Conclusions: BO after HSCT in the pediatric population has a high incidence and mortality rate. In terms of overall response and tolerability, this study showed relevant improvements in the prognosis of children with BO after the introduction of IM. Further prospective studies among children are needed to confirm these results.